Government funded suicide prevention in Australia - an environmental scan - Bridget Bassilios; Dianne Currier; Karolina Krysinska; David Dunt; Anna Machlin; Danielle Newton; Michelle Williamson; Jane Pirkis (BMC, 2024)
Abstract Background Suicide is a worldwide public health problem. In response to this problem, Australia was one of the first countries to develop national suicide prevention policy. Guided by the National Suicide Prevention Office (NSPO), which was established in 2021, suicide prevention in Australia is in a period of reform. The NSPO is driving a nationally consistent and integrated approach to suicide prevention including leading the development of a new National Suicide Prevention Strategy. This article summarises findings from an environmental scan of government-led suicide prevention in Australia, conducted as an input for the development of the new Strategy. Methods The scan was conducted from August 2022 to January 2023. We searched relevant government websites and Google to identify policy documents and programs and services. We undertook a desktop review of documents and programs/services using coding templates developed to address the objectives of the scan. Qualitative information was extracted in a systematic manner using these templates. Results Australia's suicide prevention efforts are significant as demonstrated by activities ranging from policy documents intended to guide and plan activity, the National Mental Health and Suicide Prevention Agreement committing the Federal Government and jurisdictions to work together, and the availability of national, state, local area based, and digital services and programs. Suicide prevention approaches in Australia are mostly selective or indicated. There is less emphasis on universal approaches, wellbeing promotion, strengthening protective factors and mitigating the impact of known drivers of distress. In addition, there is limited evidence to demonstrate a whole-of-government or whole-of-system approach is operating in Australia. Findings should be interpreted in the context that suicide prevention in Australia is currently in a period of transition. Conclusions Current government emphasis on and investment in suicide prevention activity, together with strong commitment to lived experience and cross sectorial collaboration, are substantial and appropriate. There are also many opportunities to further progress cross-portfolio and cross-jurisdiction suicide prevention and response efforts. This requires urgently adopting a shared understanding of suicide, which includes the diverse drivers of suicidal distress, and improving protective factors and social wellbeing.